1997
DOI: 10.1159/000267986
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Changes in Retinas of Spontaneously Hypertensive Rats Demonstrated by Corrosion Casts

Abstract: The changes in the capillary network of the retina in spontaneously hypertensive rats (SHR) were demonstrated by scanning and transmission electron microscopy. Corrosion casts with scanning electron microscopy provided a three-dimensional view of the microvasculature of the rat retina and could detect the conspicuous features of the retinal vasculature in SHR. In general, when hypertension lasted for 6–7 months in SHR, tortuosity of the retinal vessels was noted, and later the SHR retina showed increased tortu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…Quantification of the ratio of arteriolar to venous diameter revealed a slightly reduced ratio in obese vs. lean animals. Although ocular vasculopathy with narrowing of microvessels has been described in spontaneously hypertensive rat strains, 39 this result may suggest that features of metabolic syndrome aggravate the microvascular changes in this model. Nevertheless, the technique we employed considered only one aspect of microangiopathy in a circumscribed area of the rat retina.…”
Section: Discussionmentioning
confidence: 71%
“…Quantification of the ratio of arteriolar to venous diameter revealed a slightly reduced ratio in obese vs. lean animals. Although ocular vasculopathy with narrowing of microvessels has been described in spontaneously hypertensive rat strains, 39 this result may suggest that features of metabolic syndrome aggravate the microvascular changes in this model. Nevertheless, the technique we employed considered only one aspect of microangiopathy in a circumscribed area of the rat retina.…”
Section: Discussionmentioning
confidence: 71%
“…This data, revealing progressive microvascular damage, is supported by several clinical and experimental studies showing progressive capillary closure accompanied by an increased resistance and resulting decrease of perfusion in hypertensive humans [21][22][23] and various animal models. [24][25][26][27] In animal models, capillary closure was found to be reversible within the first few weeks, but became irreversible due to structural changes of the vessel wall in the course of time, thus resulting in a permanently increased flow resistance. [24][25][26][27] Even though we found a decrease of capillary den- Based on the ophthalmoscopically visible alterations, several classifications of hypertensive fundus changes have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27] In animal models, capillary closure was found to be reversible within the first few weeks, but became irreversible due to structural changes of the vessel wall in the course of time, thus resulting in a permanently increased flow resistance. [24][25][26][27] Even though we found a decrease of capillary den- Based on the ophthalmoscopically visible alterations, several classifications of hypertensive fundus changes have been proposed. [28][29][30] In clinical routine, the widespread classification of Keith and Wagener 31 has been a standard for grading fundus changes in patients with arterial hypertension for more than 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…In spinotrapezius muscle, Engelson et al reported almost twice as many transverse arterioles with shorter branches per unit tissue volume (Engelson et al, 1986). In adult SHR retinas, microvascular networks display abnormal patterning characterized by increased arteriovenous crossings and loop formation (Bhutto et al, 1997). Even in their hallmark paper identifying rarefaction in the cremaster muscle of the SHR, Hutchins and Darnell documented an increased arteriolar tortuosity (Hutchins and Darnell, 1974) and increase in the number of smallest venules.…”
Section: Microvascular Pattern Alterations In Hypertensionmentioning
confidence: 99%